PENDAMPINGAN TENTANG PENCATATAN AKUNTANSI DAN LAPORAN KEUANGAN PESANTREN SESUAI STANDAR AKUNTANSI KEUANGAN - Lidya Primta Surbakti; Yeni Elfiza Abbas; Ranti Nugraheni; Ekawati Jati Wibawaningsih (Bajang Institute, 2022)
This community service activity aims to provide assistance on accounting records and financial reports of Islamic boarding schools according to financial accounting standards. With this assistance, it is hoped that the managers of Islamic boarding schools will gain knowledge about accounting for Islamic boarding schools reporting. With the increased understanding and skills of Islamic boarding school managers, it is hoped that they can implement Islamic boarding school accounting standards or PSAK 45 in maintaining the going concern of Islamic boarding schools. The activity of mentoring the accounting reporting of Islamic boarding schools and carried out at the manager of the